PERKEMBANGAN PESANTREN DI INDONESIA - Zainal Arifin (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2012)
This research is a library research which aims to describe the development of pesantren in Indonesia and how pesantren to address a tradition. The results showed that pesantren review of the way of addressing the tradition of divided into three, namely Salafi, Khalafi, and Modern. Every pesantren has traditions that are a little different. The difference is only in its emphasis on the tradition of the study of classical books and pesantren attempt in the face of the development of science and technology. In its development, an emerging Islamic College model named Ma’had Aly. These institutions want to provide methodologies and general knowledge for graduated students of Salafi-Traditionalists, who generally have disadvantages in the field of methodology and Sciences.